Fractionation of Lignocellulosic Biomass Using Biphasic System - Christian
Palm oil is a superior crop in Indonesia. Palm oil and fruit are used as raw material for the production of palm oil (CPO) and core oil (PKO). Increased production of CPO and PKO in Indonesia also increases the volume of oil palm empty fruit bunches (TKS). In 2016, the total production of TKS waste was 33 million tons with an increase of 2 million tons annually. The component of lignocellulose biomass in TKS can be utilized as a highvalue product through the fractionation method. The purpose of this study was to determine the monophasic, one and two system, biphasic, determine the composition and operating conditions, and compare the types of solvents to cellulose, hemicellulose, and lignin. The evaluation room of the study was the empty bunches used originating from Riau, which included an acid: alcohol: water (%-v) composition of 20:60:20 (variant 1) and 25:50:25 (variant 2), operating temperature 140 and 180 ° C, time stay 80 minutes, also liquid / solid ratio 8: 1. In this experiment biomass fractionation was carried out by a single phase selective depolymerization method using hydropobic organic solvents and acid catalyst format. First, the sample consists of oil palm empty bunches smoothed and reduced in size by grinding. Next, the sample is inserted into the reactor and heated to reach operation according to the variation of the experiment. Product results from experiments and initial characterization of experiments were done by using US NREL (National Energy Renewable Laboratory) procedures. The experimental results show that the use of biphasic systems is better than monophasic systems based on the agreement of higher lignocellulosic components and in terms of permitting operation. In addition, n-butanol solvents can be used as the best lignin solvents along with acidic catalysts compared to ethanol or GVL. First variant with the operating temperature at 140oC selected as the optimal variation through a simple economic assessment with the help of ASPEN HYSYS v.10 software